Grenzgänge wissenschaftlicher Reflexivität in Judentum, Christentum und Islam - Machka, Felix; Tugrul, Kurt; Rogers, Christoph; Müller, Johannes (Wissenschaftliche Buchgesellschaft (wbg), 2023)
Theology is the science of the incomprehensible. Understood as an independent university discipline, it offers multifaceted perspectives that require not only an interdisciplinary but also an epistemological balancing act. Scientific theology in this sense is always exchange, reflection, encounter, and positioning as well as a form of transcendence. In thirteen contributions, the international authors shed light on the phenomenon of theology as an independent scientific discipline from different disciplinary, but also epistemological and religious points of view, which always oscillates between tradition, its own reflexivity and its relation to the world. The common characteristic feature is the border crossing along the intangible. The volume was produced in the context of the DFG-funded Research Training Group 1728 Theology as Science at the Goethe University Frankfurt am Main.